The Influence of Career Development and Servant Leadership towards Job Satisfaction and Employee Performance on PDAM Tirta Kencana Samarinda - Aulia Rahman; Muhammad Saleh Mire; Irsan Tri Cahyadinata (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Career development and leadership that serve for employees within the scope of the company's organization where they work are very important to be applied because it will lead to or create job satisfaction felt by employees which in the end will certainly lead to an increase in overall company performance and organization. When a good career is not created or achieved in the future, it will have an impact on job satisfaction and when it does not have a leader who serves the needs of its employees, it will also affect the perceived job satisfaction so that it affects the increase and decrease in employee performance. The purpose of this study was to prove the effect of career development and servant leadership on job satisfaction then career development and servant leadership on employee performance. The population used in this study were employees of the Regional Public Company for Drinking Water Tirta Kencana Samarinda with sample size of 200 respondents. This study using quantitative method with data analyse is structural equation modeling or CB-SEM with support software IBM SPSS AMOS 26 in processing data. The results of this study indicate that career development has a significant effect on job satisfaction; servant leadership has no significant effect on job satisfaction; job satisfaction has a significant effect on employee performance; career development has a significant effect on employee performance; and servant leadership has a significant effect on employee performance.